Obtención de concreto de alta resistencia mediante la adición de microsílice y superplastificantes en la mezcla, para su aplicación en elementos estructurales. - Cayambe Cayambe, Mario Enrique (2013)
The present research work presents the concerning to a concrete high strength (CAR) dosed with typical materials of the province of Chimborazo and business additives, this high strength concrete is of great importance for the structural evolution of large structures like big buildings and bridges. In the research procedures were developed to follow to obtain a concrete high strength, in addition the standards and specifications must be bound to each of the used materials and the methods of test that are presented.